ANALISIS TINGKAT KERUSAKAN JALAN MENGGUNAKAN METODE INTERNATIONAL ROUGHNESS INDEX (Studi Kasus: Jl. Raya Tajem Yogyakarta) - Muhammad Galih Ramadani (JURNAL ILMIAH NUSANTARA, 2025)
Roads are very important infrastructure in transportation. Therefore, the condition of the road pavement is the main factor that becomes the center of attention. Technically, road damage indicates a condition where the road is no longer able to provide optimal service. The method used to determine the value of road damage is the IRI methods, the IRI method is used to assess the unevenness of the road surface, Based on the results of the study, the average results of the evaluation of the condition of flexible pavement on the 3.50 Km Tajem Highway section based on the the IRI method were good conditions of 0.00% and 62.86%, moderate value of 22.00% and 37.14%, light damage worth 37.14% and 0.00%, and there was no heavy damage. For holes, namely leveling, wheel marks, namely leveling, lowering, leveling, and detachment, repairs can be in the form of paving. In addition to repairing the damage, additional non-structural layers can be made to improve the contours of the road and the quality of driver services.